Malaysian SME performance and the government business support services: The moderating effects of absorptive capacity - Jauriyah, Shamsuddin (2014)
This study examined the relationship between the Government Business Support Services (GBSS) (relating to financial support and non-financial support) and the performance of Small and Medium Enterprises (SMEs) in Malaysia. Due to the recognition of the importance of SMEs to the economy, numerous government programmes have been and are being implemented over the years, all of which are aimed at the development of SMEs and enhancing their performance. However, the effect of globalisation has attracted big players to operate their businesses in Malaysia. Thus coupled with the government‘s open-door policy, this has caused a relatively greater competitive and dynamic business environment for all SMEs, which makes it even more challenging for these SMEs to prosper. This research also examined absorptive capacity (AC) as a moderator variable influencing the relationship between GBSS and SME performance. AC influences the knowledge that can be assimilated and how it is used, determining which strategic actions need to be implemented, and in this study, it refers to the acquisition and assimilation of knowledge. A self-administered questionnaire was used to collect data from 150 SME firms in the northern states of West Peninsular Malaysia in April and May 2013, and the gathered data was analysed by using SPSS 19.0. Statistically, the results confirmed that GBSS is positively related to SME performance and there is an interaction of AC as a moderator on GBSS and SME performance. The outcome of this study provides new knowledge and important insights for government agencies, such as SME Corp., to look further at the programmes and guidelines, and enforce new policies toward improving the performance of SMEs in Malaysia. Finally, in order to evaluate SME performance, it is more relevant to explore the types of assistance provided by the government. Further research can provide deeper explanations by considering either financial or non-financial only factors as variables that determine SME performance